Effect of an auxiliary acceptor on D–A–π–A sensitizers for highly efficient and stable dye-sensitized solar cells. Issue 33 (4th August 2016) - Gao, Yuting; Li, Xing; Hu, Yue; Fan, Yeli; Yuan, Jianyong; Robertson, Neil; Hua, Jianli; Marder, Seth R.
Abstract : As one of the promising photovoltaic technologies, high performance metal-free dye-sensitized solar cells (DSSCs) have been explored due to the fact that they can be potentially produced using low-cost materials, their color can be tuned and they exhibit reasonable stability. Abstract : As one of the promising photovoltaic technologies, high performance metal-free dye-sensitized solar cells (DSSCs) have been explored due to the fact that they can be potentially produced using low-cost materials, their color can be tuned and they exhibit reasonable stability. Here three new organic donor–acceptor–π–acceptor (D–A–π–A) sensitizers (B-87, Q-85 andQ-93 ), containing benzothiadiazole and two new modified pyrido[3, 4- b ]pyrazines as the auxiliary acceptor, have been synthesized and employed in DSSCs. Among the three dyes, B-87 andQ-85 showed good photovoltaic performance with power conversion efficiencies (PCE) up to 10.2% and 10.0%, respectively, which contribute to the few examples of DSSCs synthesized using pure organic dyes with an iodine electrolyte to exceed the 10% efficiency barrier. It is noteworthy that an initial PCE of 7.16% has been achieved forB-87 based DSSCs with an ionic liquid electrolyte, which retained 95% of the initial efficiency after continuous light soaking for 1000 h at 60 °C, thus demonstrating outstanding stability. The molecular design strategy provides an effective approach to modulate the energy of the absorption bands as well as modify the optoelectronic and physical properties of the organic sensitizers to achieve highly efficient and stable sensitizers.